Maslow’s and Beauvoir’s Theories Portrayed on Sarah’s Character - Rahmajati, Viona Edgar; Widyaningrum, Agnes (LPPM Universitas Bumigora Mataram, 2024)
The purpose of this research is to analyze the portrayal of feminine slavery in